2-Methyl Nonyl Ketone From Houttuynia Cordata Thunb Alleviates LPS-Induced Inflammatory Response and Oxidative Stress in Bovine Mammary Epithelial Cells - Wang, Nan; Zhu, Yanbin; Li, Dandan; Basang, Wangdui; Huang, Yiqiu; Liu, Kening; Luo, Yuxin; Chen, Lu; Li, Chunjin; Zhou, Xu (Frontiers in Chemistry, 2022)
Mastitis is one of the most common diseases in dairy cows, causing huge economic losses to the dairy industry every year. Houttuynia Cordata Thunb (H.cordata) is a traditional Chinese herbal medicine that is widely used in clinical treatment. However, the therapeutic effect of 2-methyl nonyl ketone (MNK), the main volatile oil component in the aqueous vapor extract of H.cordata, on mastitis has been less studied. The purpose of this study was to investigate the protective effect and mechanism of MNK against lipopolysaccharide (LPS)-induced mastitis in vitro. The results showed that MNK pretreatment of the bovine mammary epithelial cell line (MAC-T) enhanced cell viability and inhibited LPS-induced reactive oxygen species (ROS) production and inflammatory response. MNK reduced the production of pro-inflammatory cytokines such as interleukin (IL) and tumor necrosis factor-α (TNF-α) by repressing LPS-induced activation of Toll-like receptor 4-nuclear factor-κB (TLR4-NF-κB) signaling pathway. In addition, MNK protected cells from inflammatory responses by blocking the downstream signaling of inflammatory factors. MNK also induced oxygenase-1 (HO-1) production by Nuclear factor erythroid 2-related factor 2 (Nrf2) pathway through AKT and ERK pathways, thereby reducing LPS-induced oxidative damage for MAC-T cells. In conclusion, MNK played a protective role against LPS-induced cell injury. This provides a theoretical basis for the research and development of MNK as a novel therapeutic agent for mastitis.